O20 Home sampling through social network websites: can we reduce undiagnosed HIV?. (23rd May 2012) - Elliot, E; McCowan, A; McCormak, S; Rossi, M; Van Every, T
Abstract : Background: Approximately 1 in 20 men who have sex with men (MSM) in London has undiagnosed HIV. It is a national priority to minimise time spent undiagnosed to reduce morbidity, mortality and onward transmission. Sigma reported that 29% of MSM recruited online in 2008 had never tested. We piloted an offer of home HIV sampling for MSM in partnership with the Gaydar social network website. Objectives: The objectives of the pilot were to determine (1) uptake of an online HIV risk self-assessment (2) uptake of offer for home testing (3) the proportion of those completing the assessment that is high risk. Methods: Each day 200 MSM in London were invited by Gaydar to assess their HIV risk. "High risk" was defined as unprotected anal sex (UAI) with HIV + partner or of unknown HIV status. Following assessment but regardless of risk, users were offered a postal HIV salivary sampling kit. Reactive results were confirmed in the clinic. Data were analysed using Google Analytics. Results: 4500 invites were issued between 7 November 2011 and 11 January 2012. 363 (8%) clicked through to the project website, 321 (88%) of whom completed the HIV risk assessment. Of these, 146 (45%) were defined as "high risk". 209 clicked through for information on home sampling, 82 (39%) of whom had never HIV tested. 132 test kits were requested, 73 (55%) were returned, 4 of which were new HIV diagnoses (3% of kits sent and 5.5% of samples returned). Discussion: Although low, the uptake appears to reach a population "less tested" than the population that took part in the Sigma online survey or typical of GUM clinics. The level of risk identified was similar to a clinic population with almost half reporting UAI. 55% of kits were returned and we report 5.5% or 1:18 new diagnoses. The project is now scaling up to message all 120 000 Gaydar users in Central London over 12 months and aims to provide evidence to inform the potential roll out of online strategies to enhance community based HIV testing in the UK.